[Image 07] - Smith, Captain Sir William [?ob. 1732] (My University, 1801)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View from ground adjacent to Malin Head looking toward down off head and the entrance into Lough Swilly drawn by Sir Wm Smith in 1801.
Keywords: Malin Head; Lough Swilly; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810